Structured Chemical Safety Multimedia Courseware For Secondary Schools Chemistry Teachers - Prabadevi, Narayanasamy (2014)

(untitled)
Interactive multimedia courseware is one of the modalities that being implemented in self-teaching with attentive features which make adult learning interesting and effectives. The study aims is to establish interactive multimedia courseware that empowers national secondary schools chemistry teachers with adequate knowledge for safe conduct of chemistry practical’s by students. Perisian multimedia interaktif adalah salah satu kaedah berasaskan teknologi maklumat yang digunakan dalam pengajaran kendiri dengan ciri-ciri prihatin yang dibangunkan berdasarkan pembelajaran yang menarik dan berkesan. Kajian ini bertujuan untuk membina sebuah perisian khas untuk para guru kimia di sekolah menengah kebangsaan Malaysia bagi meningkatkan pengetahuan mereka mengenai keselamatan kimia di makmal sekolah.